2021
DOI: 10.1186/s40643-021-00445-8
|View full text |Cite
|
Sign up to set email alerts
|

Biological pretreatment of corn stover for enhancing enzymatic hydrolysis using Bacillus sp. P3

Abstract: The biological pretreatment for the enzymatic hydrolysis of lignocellulosic biomasses depends exclusively on the effective pretreatment process. Herein, we report a significant enhancement of enzymatic saccharification obtained with corn stover using a bacterial strain Bacillus sp. P3. The hemicellulose removal from corn stover by the strain Bacillus sp. P3 was evaluated for enhancing subsequent enzymatic hydrolysis. Therefore, our study revealed that an alkaline-resistant xylanase as well as other enzymes pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…At different time points (10,20,30,40, and 60 days) of incubation, the flasks were withdrawn in duplicate, and the contents were mixed with distilled water. The crude enzyme extract (CEE) was then extracted from the mixture as described in section 2.3.…”
Section: Biological Pretreatment Reaction Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…At different time points (10,20,30,40, and 60 days) of incubation, the flasks were withdrawn in duplicate, and the contents were mixed with distilled water. The crude enzyme extract (CEE) was then extracted from the mixture as described in section 2.3.…”
Section: Biological Pretreatment Reaction Systemmentioning
confidence: 99%
“…Some research groups have explored co-culturing techniques using commercially known laccase (C. comatus) and xylanase (T. reesei) producers, achieving peak productivities of 2180 U/ml and 160 U/ml, respectively, after 5 days of incubation [29]. The early appearance of high levels of laccases and hemicellulases during fermentation facilitates the delignification process and reduces the duration of biological treatment [30]. The availability of high titers of lingo-hemicellulases at the early stages of fermentation appears to be advantageous for the biological pretreatment of corn stover.…”
Section: Microorganismmentioning
confidence: 99%
See 1 more Smart Citation
“…The biomass composition analysis was performed as mentioned in Wu et al (2021), in which cellulose and hemicellulose were analyzed by measuring the glucan and xylan contents. The Klason lignin analysis was performed by anthrone-sulfuric acid and orcinolhydrochloric acid methods.…”
Section: Biomass Composition Analysismentioning
confidence: 99%
“…Moreover, the study revealed Bacillus sp. produced maximum CMCase (17.8 U g -1 ) and xylanase (195.8 U g -1 ) from corn stover (0.5% w/v) among the various biomasses and they used corn stover for further study (Wu et al 2021).…”
Section: Production Of Cmc and Xylan Hydrolysing Enzymesmentioning
confidence: 99%